The effect of agricultural bank loans on agricultural production in Syria during the period (2000-2020( (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The research aimed to know the impact of the agricultural bank on agricultural production in Syria, and the three forms of loans (short, medium, and long-term) were taken as independent variables, and agricultural production as a dependent variable, the descriptive analytical approach was adopted, and the impact was measured using time series during the period 2000-2020 The use of statistical methods, namely the stability of time series, co-integration and causation, building a standard model for the independent variables and their relationship to the dependent variable, and the tool used in the analysis, the Eviews program.The research reached the most important results:- There is no statistically significant effect at the significance level (a < 0.05) for short-term loans on agricultural production in the long term, while it was found that there was an effect in the short term.- There is no statistically significant effect at the level of significance (a < 0.05) for medium-term loans on agricultural production in the long term, while it was found that there was an effect in the short term.- There is no statistically significant effect at the significance level (a < 0.05) for long-term loans on agricultural production in the long term, while it was found that there was an effect in the short term.